Vasopressin augments TNBS‐induced colitis through enteric neuronal V1a receptor‐mediated COX‐2‐dependent prostaglandin release from mast cells in mice. Issue 2 (18th October 2018) - Dou, Dandan; Chen, Lixin; Di, Hong; Song, Zhuoran; Li, Shirui; Bu, Xinjie; Dai, Qing; Wang, Shuai; Li, Jing Xin; Zhu, Xiaolong; Jing, Haiyan
Abstract: Background: Inflammatory bowel disease (IBD) is a functional disorder with chronic and relapsing clinical features. Vasopressin (VP) is a hormone responsible for water and stress homeostasis and also regulates gastrointestinal inflammation and motility. We explored whether VP was related to IBD pathogenesis and its possible pathway. Methods: Colitis was induced by 2, 4, 6‐trinitrobenzenesulfonic acid (TNBS) in mice. The disease activity and colonic damage were evaluated through a scoring system. Locations of the V1a receptor were revealed by immunochemistry method in colon. Ussing chamber technique was performed for the electrophysiological characterization by using rat ileum. The (Arg 8 )‐Vasopressin (AVP)‐evoked short‐circuit current ( Isc ) was recorded in the presence of conivaptan (V1a and V2 receptor antagonist), tolvaptan (V1b receptor antagonist), tetrodotoxin (TTX), atropine, cyclooxygenase (COX) inhibitors (indomethacin, nonspecific COX antagonist; SC560, COX‐1 antagonist; NS560, COX‐2 antagonist), and a stabilizer of mast cell (cromolyn sodium), respectively. Key Results: TNBS resulted in the obvious loss of body weight and tissue damages in mice. AVP significantly aggravated the TNBS‐induced colitis, which was attenuated by conivaptan but not tolvaptan. V1a receptors were found immunopositive in neurons among the enteric nervous system. AVP evoked a pulsatile response in Isc . Its amplitude, frequency, and cycle duration were around 8‐15 µA/cm 2, 10‐11 mHz, and 1.5 minutes, respectively. Notably, the AVP‐evoked change in Isc was abolished by TTX, atropine, conivaptan, indomethacin, NS560, and cromolyn sodium, respectively. Conclusions and Inferences: VP‐V1a receptor played the proinflammatory role in TNBS‐induced colitis by promoting COX‐2‐dependent prostaglandin release from mucosal mast cells, which was mediated by the cholinergic pathway. Abstract : Vasopressin augments the TNBS‐induced colitis, which is mediated by prostaglandin release from the cholinergic terminals surrounding the mast cells in the mucosa. This result might lead to a deeper comprehension and treatment targets for the exacerbation or relapse of inflammatory bowel disease in ordinary life caused by acute psychological stress.